"The guy is blind but appears normal according to diagnostic parameters": a reflection on racism, whiteness, and the 'neutrality' of technology in the biomedical field in Brazil. Issue 2 (3rd April 2023) - Muniz, Tatiane
ABSTRACT: Rejected a priori in the biomedical field as a category that has no meaning for clinical practice, race maintains an absent presence that spans techno-scientific productions and the daily practices of health professionals. Race constitutes a type of infrastructure that is rarely treated critically and that can be given as supporting evidence in scientific practices. It appears as an unexpected effect of biomedical technology that is actually centered around ideals of whiteness that it projects as universal. This exposes the limitations of biomedical technology to reach 'other bodies'—those that are not white – labeled as resistant to biotechnological intervention. By looking at ultrasound performance in diagnostic testing for glaucoma, this article discusses how whiteness, racism, and technological 'neutrality' are articulated in the materialization of race in diagnostic technological devices and health intervention in Brazil.